Strategi Peningkatan Profitabilitas UMKM Makanan dan Minuman di Kota Palu - Nurhayana, Nurhayana; Kadang, Juliana; Darman, Darman; Samudra, Suryadi (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The purpose of this study was to examine approaches used to increase the profitability of food and beverage MSMEs in Palu City. The sample used was 40 MSMEs. Data collected through questionnaires and interviews were then analyzed using multiple linear regression. The findings indicate that digital marketing have the greatest impact on MSME profitability, followed by financial management and product innovation. Social media and e-commerce are two examples of effective digital marketing techniques that can increase target market awareness and company revenue. Furthermore, efforts to maintain company stability and competitiveness are facilitated by innovative product development and sound financial management. A combination of these three strategies is recommended to significantly increase MSME profitability.